Gambaran Strategi Pembelajaran Instruktur pada Program Kursus Bahasa Inggris di Hem's Institute Kota Padang - Indah Yulianda; Vevi Sunarti (Universitas Negeri Padang, 2018)
This research is distributed by high motivation learn to citizens studying at language courses program in Hem's Institute city of Padang. Researchers suspect that the learning motivation of high learning citizens due to the instructor in the learning strategies learning activities. Type of this research is quantitative descriptive research. The population in this research is to study language courses which amounted to 110 people. Samples taken many as 28 people. Data analysis techniques using the formula percentages. The research results indicate (1) the determination of the expected changes to the citizens learning instructors are categorized good, (2) the determination of which approach to use the trainer to the citizens learn categorized good, (3) the determination of the methods used instructor to the citizens learn categorized good, and (4) the setting of norms of the success of the instructor to the citizens learn categorized good. Keywords: Learning Strategies, Motivation of Learning, Courses, Instructor